Posttranscriptional Suppression of Lipopolysaccharide-Stimulated Inflammatory Responses by Macrophages in Middle-Aged Mice: A Possible Role for Eukaryotic Initiation Factor 2α - Ken Shirato; Kazuhiko Imaizumi (International Journal of Inflammation)
The intensities of macrophage inflammatory responses to bacterial components gradually decrease with age. Given that a reduced rate of protein synthesis is a common age-related biochemical change, which is partially mediated by increased phosphorylation of eukaryotic initiation factor-2α (eIF-2α), we investigated the mechanism responsible for the deterioration of macrophage inflammatory responses, focusing specifically on the age-related biochemical changes in middle-aged mice. Peritoneal macrophages isolated from 2-month-old (young) and 12-month-old (middle-aged) male BALB/c mice were stimulated with lipopolysaccharide (LPS). Although LPS-stimulated secretion of tumor necrosis factor-α (TNF-α) by the macrophages from middle-aged mice was significantly lower than that from young mice, LPS caused marked increases in levels of TNF-α mRNA in macrophages from middle-aged as well as young mice. Moreover, LPS evoked similar levels of phosphorylation of c-Jun N-terminal kinase (JNK) and nuclear factor-κB (NF-κB) in young and middle-aged mice. In contrast, the basal level of phosphorylated eIF-2α in macrophages from middle-aged mice was higher than that in macrophages from young mice. Salubrinal, an inhibitor of the phosphatase activity that dephosphorylates eIF-2α, suppressed the LPS-stimulated inflammatory responses in a murine macrophage cell line RAW264.7. These results suggest that posttranscriptional suppression of macrophage inflammatory responses during middle age requires phosphorylation of eIF-2α.